Vitamin D receptor gene BsmI polymorphisms in Egyptian children and adolescents with systemic lupus erythematosus: A case–control study. Issue 46 (November 2016) - Azab, Seham F.; Ali, Yasser F.; Farghaly, Mohsen A.A.; Hamed, Mohammed E.; Allah, Mayy A.N.; Emam, Ahmed A.; Abdelsalam, Nasser I.; Hashem, Mustafa I.A.; Gawish, Heba H.; Nabil, Rehab M.; Kamel, Lamiaa M.; Fahmy, Dalia S.; et al.
Abstract : Abstract: Systemic lupus erythematosus (SLE) is a multisystemic autoimmune disease. The vitamin D receptor (VDR) gene is a candidate gene for susceptibility to autoimmune disorders. To date, only a few studies concerned the association of the VDR gene polymorphisms with childhood-onset SLE. In this study, we aimed to investigate the BsmI polymorphisms in the VDR gene, for the first time in Egyptian children and adolescents with SLE, to determine whether this polymorphism could be a marker of susceptibility to or severity of SLE and we also measured the serum level of 25-hydroxyvitamin D (25[OH] D) to assess its relation to such polymorphism. This was a case–control study including 100 patients with SLE and matched with age, sex, and ethnicity and 100 healthy controls. All subjects were genotyped for the VDR gene BsmI polymorphism by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP), whereas the serum 25(OH) D levels were measured by enzyme-linked immunosorbent assay method. Compared to the contros subjects, the VDR BsmI BB genotype and B allele were overrepresented among SLE patients (odda ratio [OR]: 5.5; 95% confidence interval [CI]: 1.9–15.9; P  = 0.002 and OR: 1.84; 95% CI: 1.21–2.80; P  = 0.003; respectively). We found a significant association between VDR BsmI BB genotype with lupus nephritis (OR: 6.8; 95% CI: 1.18–50.5; P  = 0.001). However, we did not observe any significant association of studied polymorphisms with other clinical manifestations, laboratory profiles of SLE, or disease activity score. Our data revealed no association between VDR BsmI genotypes or alleles and serum 25-hydroxyvitamin D levels among studied patients with SLE (all P  > 0.05). We demonstrate for the first time, to the best of our knowledge, that the VDR BsmI gene polymorphisms may contribute to susceptibility to SLE in Egyptian children and adolescents. Moreover, we found that the BB genotype constituted a risk factor for the development of nephropathy among studied patients with SLE. However, we did not find any significant association of the VDR BsmI gene variants with other clinical manifestations, laboratory profiles of SLE, disease activity index score, or serum 25-hydroxyvitamin D levels.